2006
DOI: 10.1111/j.1399-3046.2006.00459.x
|View full text |Cite
|
Sign up to set email alerts
|

Unexpectedly high prevalence of pretransplant abnormal glucose tolerance in pediatric kidney transplant recipients

Abstract: Several studies suggested that the incidence of new-onset diabetes following pediatric kidney transplantation has increased markedly in recent years, with reported incidence of up to 20%. However, limited information is available regarding the incidence and features of pretransplant status of abnormal glucose tolerance in pediatric kidney transplant recipients. We assessed the risk of 55 non-diabetic pediatric transplant recipients developing PTDM by performing OGTT prior to transplantation. For post-transplan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 29 publications
(38 reference statements)
0
23
0
2
Order By: Relevance
“…The majority of pediatric studies have demonstrated a high prevalence of insulin resistance ranging from 16 to 47% in patients with CKD [10,11,34]. In contrast, a few pediatric studies have demonstrated inadequacy in both early-phase and late-phase insulin secretion in end stage renal disease [12,13]. Our study demonstrates that the pre-dialysis patients had a high prevalence of insulin resistance of 35%.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…The majority of pediatric studies have demonstrated a high prevalence of insulin resistance ranging from 16 to 47% in patients with CKD [10,11,34]. In contrast, a few pediatric studies have demonstrated inadequacy in both early-phase and late-phase insulin secretion in end stage renal disease [12,13]. Our study demonstrates that the pre-dialysis patients had a high prevalence of insulin resistance of 35%.…”
Section: Discussionmentioning
confidence: 64%
“…Although most studies performed on pediatric patients have focused on post-transplant patients, a few studies have shown that up to 45% of CKD patients exhibit glucose intolerance [13,29]. Abnormalities in glucose and insulin metabolism in uremia are mainly associated with the accumulation of "uremic toxins", vitamin D deficiency, metabolic acidosis, anemia, and inflammation [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Araştırmacılar, HOMA-IR'ye dayalı hiperinsülinemi ve insülin direncinin hafif-orta böbrek yetersizliği olan yetişkinlerde görüldüğünü göster-mişlerdir. [15][16][17][18][19] Bizim çalışmamızda da, hem TNF-α düzeyleri hem de insülin direnci KBY'li hastalarda sağlıklı kontrollere göre daha yüksek tespit edilmiştir (p< 0,001).…”
Section: Discussionunclassified
“…Apart from causing CVD, they also have direct renal damaging effects [12] . However, apart from one previous study in mild to moderate pediatric CKD [14] , the insulin levels and insulin resistance in the pediatric CKD population has previously only been described in a few small studies of adolescents with severe renal failure [15][16][17][18][19] . Recently, they have also been found to be linked to malnutrition [20,21] and inflammation [14,22] , two other well-known cardiovascular risk factors.…”
mentioning
confidence: 99%